G267 Instigation of routine monitoring in babies in a myanmar hospital. (May 2019) - Parbery-Clark, C; Aung, ZN; Wah, W; Win, M
Abstract : Background: Neonatal mortality in Myanmar is substantial at 26.4 per 1000 births in 2015 1 with neonatal sepsis contributing in over 18%. 2 A fundamental part of caring for newborns in the immediate period post-delivery is the identification of babies who require active monitoring and those who need Neonatal Unit (NNU) admission. Measuring and documenting vital signs play a key part in identifying stable or deteriorating babies. Aims/methods: In the Neonatal Unit (NNU) in a Myanmar hospital, temperature was the sole vital sign being measured. Therefore substantial system weaknesses were present surrounding the monitoring of babies to identify those who were becoming sick or indeed sicker to aid timely assessment and treatment. Consultation between all levels of staff allowed a mutually agreed revised frequency of vital signs (observations) for the babies in the NNU. The target was 70% of vital signs being measured in accordance to the agreed schedule. Practical staff training about how to measure vital signs with the use of the newly implemented Emergency Paediatric Care Program observations charts (which allowed more than temperature documentation) was rolled out. Subsequent reviews of the observation charts facilitated residual implementation problems to be ironed out with a collaborative solution finding approach with local staff. Interventions included identification in joint consultation with the staff that due to the 24 hour shift patterns, the times of observation measurement were changed to help facilitate measurement. Results: The graph shows steady improvement from 0% of total observations being measured in accordance with the agreed schedule to 80% after 8 weeks with an almost in a dose related response with review of the data, feedback and troubleshooting collectively. There was improvement in all parameters measured during the review period. Conclusions: We show that with ongoing cycles of data and performance review with identification of barriers and specific agreed interventions, significant positive change can occur to help improve neonatal care in this hospital. It also describes a model for change in similar setting district hospitals. References: WHO Myanmar Statistic Summary 2015, Global Health Observatory Country Views. Emergency Paediatric Care Program, October 2016, Early Neonatal Care: Feeding and Warmth.